Governance of Social Data Verification in the PBI-JKN Program: A Policy Study on the Deactivation of 7.39 million Recipients by the Indonesian Ministry of Social Affairs - Rafdi, Hashfi; Fichriyadi Hastira, Muh; Reza Fahlevy, Muhammad; Jumansyah, J.; Nurmiyati, Niken (Golden Ratio of Data in Summary, 2025)
The deactivation of 7.39 million participants in the National Health Insurance Contribution Assistance Program (PBI-JKN) by the Ministry of Social Affairs in early 2025 sparked policy controversy, particularly regarding data accuracy and its impact on vulnerable groups. This study aims to analyze the governance of data verification and the implementation of this policy within the framework of Good Enough Governance proposed by Marlie S. Grindle. Through a case study in Central Java Province—covering Semarang, Demak, and Wonogiri—this research explores how local bureaucratic and fiscal capacity limitations influence responses to central government policies. The results reveal a mismatch between the central government's technocratic approach and the adaptive needs of local areas. While digitalization enhances efficiency, the lack of social sensitivity in implementation risks causing health exclusion. The theory of Good Enough Governance is relevant for evaluating policies contextually and realistically, where reforms do not have to be ideal but sufficiently effective in reaching people with low incomes. The study recommends improvements in data integration, public participation, and policies grounded in social justice. These findings will enrich the discourse on inclusive and adaptive social policy governance amid systemic limitations.